Intermediates Of Photosynthesis in Acetabularia mediterranie Chloroplasts - Bidwell, R. G. S. (1970)
The chloroplast fraction isolated from Acetabularia mediterranie was exposed to (14)CO(2) as NaH(14)CO(3) in light and darkness, and soluble radioactive compounds were analyzed at frequent intervals. The behavior of Calvin cycle intermediates indicates that this cycle was responsible for much of the carbon fixation in the chloroplasts. However, a substantial part of recently fixed carbon was metabolized via glycolic and glyceric acids. Possible pathways for their metabolism are discussed. Some carboxylation of C(3) acids was suggested by the behavior of phosphoenolpyruvate and malate. A number of amino acids were formed. Small amounts of such compounds as citrate, succinate, and fumarate not usually associated with photosynthesis might have been derived from a low level of mitochondrial contamination. About one-third of the carbon fixed in light was present in acid-labile insoluble compounds other than polysaccharides or proteins. Dark fixation of CO(2) was very small compared with photosynthesis.